1996
DOI: 10.1007/bf00579706
|View full text |Cite
|
Sign up to set email alerts
|

The role of structure-based ligand design and molecular modelling in drug discovery

Abstract: Structure-based ligand design is a technique that is used in the initial stages of a drug development programme. The role of various computational methods in the characterization of the chemical properties and behaviour of molecular systems is discussed. The determination of the three-dimensional properties of small molecules and macromolecular receptor structures is a core activity in the efforts towards a better understanding of structure-activity relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Small molecule drug designing is one of the important area in medicinal chemistry [1]. Computational tools are nontime consumable effective tools to identify efficacious drugs now a days [2].…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule drug designing is one of the important area in medicinal chemistry [1]. Computational tools are nontime consumable effective tools to identify efficacious drugs now a days [2].…”
Section: Introductionmentioning
confidence: 99%
“…Related on in silico studies have indicated molecular docking to be a robust and reliable approach to screen for drug-likeness of molecules [24][25][26]. In drug discovery, structure-based drug design is a vital tool for the discovery and development of new molecules using X-ray crystal structure of a protein from protein data bank (PDB) [27][28][29][30]. In molecular modeling, drugreceptor complex stability, exact binding mode, and ligand interaction with amino acids of the protein molecule can be visualized using various docking approaches to discover the pharmacological properties of drug molecules [31].…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided drug design uses computational chemistry to discover, enhance, or study drugs and related biologically active molecules. Structure-based drug design (or direct drug design) relies on knowledge of the three dimensional structure of the biological target obtained through methods such as x-ray crystallography or NMR spectroscopy [10][11][12][13][14] .…”
mentioning
confidence: 99%